ANALISIS POTENSI DAN SEBARAN AGROWISATA DI KABUPATEN SOLOK - Rery Novio; Azizah Qairunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to (1) Know the Potential of Agritourism in Solok Regency. (2) Know how the distribution of agro-tourism in Solok Regency. Descriptive qualitative research type. Selection of research informants by purposive sampling consisting of 6 informants, namely 2 managers, 3 visitors and 1 trader. Data collection techniques by means of field observations, interviews or interviews and documentation. Data analysis techniques from field notes, data reduction, data presentation, data verification and conclusion drawing. The results showed that agritourism in Solok Regency has the potential, namely 1) The attractions of the three attractions are beautiful and green natural scenery, parks, playgrounds, strawberry monuments and fruit picking tours and cultivation of ornamental plants. 2) Amenity, namely guard posts, toilets, parking lots, prayer rooms, stalls, entrance tickets, direction boards, rest areas, trash cans, photo spots. 3) Accessibility, namely the ease of reach to the tourist attraction, at the Sirukam Dairy Fram tourist attraction the road conditions are good and the quality of the road has been paved and access to the tourist attraction is far from the center of the highway, the Dzjikho Strawberry Garden tourist attraction is very strategic and the road conditions are still not good because the road is still gravel and not paved and access to the Alahan Panjang Tea Garden tourist attraction is relatively easy to access because the road to the tourist attraction is in the center of the highway and the road conditions have been paved. 4) Anciliary of the three attractions, namely guide services, Camping Ground (camping area), security posts, Wi-Fi, lodging or homestay. The distribution of agro-tourism in Solok district is very diverse and spread across several sub-districts with varying areas and has diversity ranging from livestock, agriculture, and plantations that make tourists make Solok district one of the tourist destinations and a unique and interesting experience for tourists.